ANALISIS STRATEGI PENGEMBANGAN WISATA PESISIR : Studi pada Dinas Kebudayaan & Pariwisata Kabupaten Pangandaran - B. Syarifuddin Latif (Universitas Nasional, 2019)
Pangandaran Regency is one of the most potential regency in West Java to develop its tourism. Pangandaran Regency has four local tourism objects governed by local Department of Tourism and Culture: Citumang, Pangandaran Beach, Green Canyon, Batu Karas Beach, Santirah, Batu Hiu Beach, Nature Reserve and Turtle Conservation. Tourism of Pangandaran offers many tourism objects whose attraction and feature are distinctive in those places. Nonetheless, the lack of attention given by the government particularly in term of promotion that has become a hurdle to the advancement of tourism in Pangandaran. Therefore, it is essential that relevant authorities must have awareness and introduce several regulations to advance the tourism development. Developing tourism sector requires strategies which equipped by well-arranged tourism developing plan in order to optimize the tourism potential. The role of local government is therefore important as the main generator and afterwards, giving the Pangandaran Regency Tourism and Culture Department full authority to create and implement tourism developing strategies. In this thesis, the writer is encouraged to acknowledge and review the role of Pangandaran Regency Tourism and Culture Department in improving the tourism potential. It is acquired by settling the statement of problem on first, the strategies of Pangandaran Regency Tourism and Culture Department to develop its tourism sector and second, the factors affecting the improvement of tourism in Pangandaran Regency. This research applied descriptive research method in nature by employing qualitative approach. The resources were grouped into two, primary data and secondary data. The data collection techniques were observation, interviews, and documentation. The collected data were analyzed by following the procedures: data collection, data presentation, and conclusion drawing.